Fungsi Kelembagaan Subak Pada Perkebunan Lada di Kecamatan Mowila Kabupaten Konawe Selatan (Studi Kasus pada Kelembagaan Subak Satu pada Tanaman Lada Hasil Konversi dari Padi Sawah di Kecamatan Mowila Kabupaten Konawe Selatan) - Isnian, Sitti Nur; Nalefo, La; Mutmainnah, Mutmainnah; Rosmawaty, Rosmawaty; Mardin, Mardin (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2018)
This study aims to look at the institutional functions of Subak in Plantation Pepper as a result of land conversion from wetland rice in Mowila Subdistrict, Konawe Selatan District. This research is qualitative. The results showed that the institutional functions of Subak on pepper plantations in Mowila Subdistrict, Konawe Selatan District were described in the Functions of Tri Hita Karana namely parahyangan with ritual activities, ulun carik, purnama nyilem, and ceremony of moving rice fields. Pawongan with the coordination of pepper farmers to Subak and contributing traditions. Palemahan is marked by the provision of two meters of land and land for sacred buildings.